The research into speed ability of fuel dispersion - Matievsky, Dmitry; Svistula, Andrey; Eskov, Alexander (Transport, 2005)
The investigation of the process of carburetion in combustion engines is an actual scientific and practical task. The results of the experimental investigations of the fuel jet flow formed by the nozzle through two section series arranged are shown in the presented article. Front speed and fuel mass speed between optical sections in fuel flow were determined by registered optical density of fuel flow for different pressures. The procedure of the determination of speed abilities of the fuel flow gives the preconditions for creating the bench for the determination of fuel sprayers in the work process of manufacturing with the aim of their division into the groups of one‐type parameters. Such approach assumes the usage of manufacturing standard that is the sprayer and the fuel pump with the best ability of injection. First Published Online: 27 Oct 2010